1995
DOI: 10.1001/archinte.1995.00430100094011
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Infection in Pregnant and Nonpregnant Women Infected With HIV in the Women and Infants Transmission Study

Abstract: These data support current Public Health Service recommendations for tuberculin skin testing in persons infected with the human immunodeficiency virus, and emphasize that evaluation should include pregnant as well as nonpregnant women. The prevalence of anergy does not appear increased in pregnancy in women infected with the human immunodeficiency virus. Health care providers should include tuberculin and anergy skin testing as part of the standard prenatal care for women infected with the human immunodeficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…BCG vaccination can also lead to TST positive results in healthy women [11],[28]. In a high HIV prevalence setting, other tests and clinical symptoms should therefore be taken into account in diagnosing TB [41] and the TST and anergy skin tests (the latter is used to evaluate whether the immune system is functioning properly or not and can indicate whether the results of the other skin test are reliable) are recommended as a TB screening method in the prenatal care procedures [31]. In populations in which the majority of people are BCG vaccinated or their vaccination status is uncertain, TST is discouraged and IGRA is recommended for TB screening and diagnosis [11],[28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCG vaccination can also lead to TST positive results in healthy women [11],[28]. In a high HIV prevalence setting, other tests and clinical symptoms should therefore be taken into account in diagnosing TB [41] and the TST and anergy skin tests (the latter is used to evaluate whether the immune system is functioning properly or not and can indicate whether the results of the other skin test are reliable) are recommended as a TB screening method in the prenatal care procedures [31]. In populations in which the majority of people are BCG vaccinated or their vaccination status is uncertain, TST is discouraged and IGRA is recommended for TB screening and diagnosis [11],[28].…”
Section: Resultsmentioning
confidence: 99%
“…Results are therefore not solid enough to be applicable to a larger population. Another limitation was that few studies had control groups; some used comparison groups that were not fully comparable with the study group [16]-[18],[20],[25],[28],[31],[39]. Furthermore, the study designs were weak, since no randomised controlled trials were present.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the risk of both LTBI and active TB was greatest among PLHIV from ethnic minorities; particularly those of black African, South Asian or Hispanic ethnicity. 13,15,17,19,23,25,31,32,37,43,44,46,49,52,53 Similarly, PLHIV who were born in, or long-term residents of, countries with high TB incidence had higher rates of LTBI and active TB. [10][11][12][13]17,18,[22][23][24]26,45,56 Few studies examined the effects of country of birth and ethnicity independently of each other; those that did found no independent associations between ethnicity and country of birth and active TB 34,46 or LTBI.…”
Section: Ethnicity and Country Of Birthmentioning
confidence: 99%
“…Prolonged debility, nutritional deficiency, lack of social support, complications of TB and need for prolonged anti-TB medications put an enormous pressure on maternal physical and mental health. 5,8,10,11,32 Although most studies suggest that pregnancy does not alter the course and outcome of TB, [35][36][37][38][39][40] the quality of controls in these studies is questionable because of the practical difficulties of finding non-pregnant controls, who could be adequately matched for the severity of disease. Progress of TB is rare during pregnancy provided the women are compliant to drug therapy.…”
Section: Diagnosis Of Tb In Pregnancymentioning
confidence: 99%